UPAYA PENINGKATAN HASIL BELAJAR PASSING ATAS MELALUI PEMBELAJARAN PERMAINAN BOLA PANAS (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
Classroom Action Research was conducted in order to determine Improved learning outcomes through learning Passing on Heat ball game on fourth grade students of SDN 02 Jajarwayang Bojong District of Pekalongan in the Academic Year 2013/2014. This study uses action research. The results showed that the learning outcomes through a learning game passing over hot ball can attract students so not boring, it is seen on mastery learning outcomes of students who exceed a predetermined KKM has increased by 70 in the first cycle in the form of mastery learning reached 37% while on cycle II passing grade is 86%.